Employing Leadership Practices in Educational Institutions According to the Organizational Structure of DNA (Journal Of Educational and Psychological Researches, 2023)
DNA, as the basis of every living cell, is one of the most important and influential scientific discoveries. This research aims to identify and compare the organizational DNA to the leadership practices of school principals in the Sultanate of Oman and to reveal the similarity between principals’ leadership practices and the structure of DNA. In addition, it intends to identify any statistically significant differences between the responses of the participants due to the study variables: gender, job title and experience. A questionnaire was designed and data were collected from a randomly selected sample composed of (100) teachers in the Sultanate of Oman. The study found limitless diversity in the characteristics of DNA of leadership and the degree of similarity of leadership traits is difficult to accurately resemble in comparison to the genetic traits (genes) in humans. The adaptation of the DNA model of leadership as a developmental approach in educational institutions is recommended